Nitrogen removal by eutrophic coastal wetlands accomplished with CH4 emission reduction. (15th January 2022) - Yang, Hualei; Chen, Xuechu; Zhang, Chunsong; Zhao, Mingming; Zhao, Xinmeng; Perry, Danielle C.; Tang, Jianwu
Abstract: Coastal wetlands play an important role in nitrogen removal and are a vital blue carbon sink. The produced methane (CH4 ) in coastal wetlands has been recently identified as a possible carbon source for denitrification process, providing a significant contribution to coastal nitrogen cycling. However, the in-situ correlation between CH4 emissions and denitrification rate, as well as their coupling mechanism is still unclear. Here, we investigated the nitrogen removal pattern throughout a complete tidal cycle, quantified the in-situ linkage between CH4 emissions and denitrification rate, and explored the associated microbial mechanisms in the eutrophic coastal wetland. The results showed that (1) the removal of nitrogen was driven by the tidal cycle (marsh flooding and drying), which involved two processes - physical interception and microbial denitrification; (2) the denitrification rate was linearly positively correlated to the CH4 emission (R 2 = 0.87, p < 0.0001); (3) nitrite- and nitrate-dependent denitrifying anaerobic methane oxidation (DAMO) coexisted in the wetland sediment, and promoted nitrogen removal by utilizing CH4 as the carbon source for denitrification. Our findings suggested that CH4 emission could enhance denitrification via DAMO in the field, and deepened the understanding of the dynamic nitrogen removal process within eutrophic coastal wetlands, and further indicated a strong interaction between coastal carbon and nitrogen cycling.